ANALYSIS OF GRID-SYSTEMS INFORMATION SECURITY ASPECTS - A. I. Trubei (Informatika)
The article presents the analysis of Grid-systems information security aspects, Also, risk assessment methods, using public databases, expert systems and statistical techniques are proposed.